PERKEMBANGAN PENDIDIKAN MASYARAKAT ASLI SUKU BONAI DI DESA BONAI KECAMATAN BONAI DARUSSALAM KABUPATEN ROKAN HULU 1999-2018 - Harefa, Titi Sugiarti; Ibrahim, Bedriati; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Bonai tribe is an isolated tribe in Riau who inhabit areas along the Rokan river with a livelihood as fishermen and gardeners. The purpose of this study is,to find out the history of the Bonai tribe in the Bonai Village. To find out the development of Bonai tribal education in the Bonai Village 1999-2018. To find out the driving factors and inhibiting factors of the education development of the Bonai indigenous people in Bonai Village. This study uses qualitative methods with data collection techniques such as observation, interviews, documentation, and literature. The results of this study indicate, (1) Bonai Tribe was brought by two brothers namely Sultan Janggut and Sultan Harimau who wandered to Brunei. (2) The development of Bonai indigenous education from 1999-2018 experienced developments in the construction of schools, students, and educators, where Bonai village has four school units. The situation of students also increases annually, especially Bonai children. (3) Factors inhibiting the development of education in the Bonai tribe are economic factors and the supporting factors is support from the government.Key Words: Development, Education of the Bonai Tribe Society